Medicina verde în practica veterinară: O alternativă sustenabilă la antimicrobiene - Larisa M. Ardelean; Florin Muselin; Alexandru Octavian Doma; Mihai Folescu; Daiana Ionela Cocos; Romeo Teodor Cristina; Eugenia Dumitrescu (Medicamentul Veterinar, 2025)
In the current global context, marked by the intensification of climate change, environmental degradation, and the alarming rise of antimicrobial resistance (AMR), veterinary medicine is facing a critical challenge: identifying sustainable alternatives to conventional treatments. In this regard, the concept of “green medicine” is gaining increasing relevance, promoting the use of natural products, phytocomplexes, and alternative therapies as complementary or substitute solutions for conventional antimicrobials. Green medicine aims not only to treat diseases effectively, but also to reduce the negative impact on the environment, lower the risk of developing antimicrobial resistance, and ensure a higher level of animal welfare. Within the One Health framework, which recognizes the close interconnection between animal, human, and environmental health, green medicine represents a promising and necessary direction for a modern, responsible, and sustainable veterinary practice.